Massive hemothorax due to intrathoracic extramedullary hematopoiesis in a patient with beta thalassemia hemoglobin E disease - Apichat Tantraworasin (2018)
Case report of a 28-year-old man with beta thalassemia/hemoglobin E disease who developed a massive hemothorax due to bleeding from multiple large intrathoracic, paraspinal hematopoietic masses. Initially, a thoracotomy was required for the control of bleeding. Postoperatively, the patient received 2,000 ml of packed red cells but he continued bleeding after the blood chemistries and coagulopathy specimen were corrected. The decision was made to return to the operating room for a thoracotomy to control the bleeding. However, before re-operating, the patient underwent a collapse and failed resuscitation. This complication has never been previously reported in Thailand.